To the problems of safe use of nonsteroidal anti-inflammatory drugs in pediatric rheumatologist practice: opportunities in local therapy - A. V. Meleshkina; S. N. Chebysheva (Сеченовский вестник)
The article deals with local therapy in the practice of pediatric rheumatologist. Separately considered the possibility of using nonsteroidal anti-inflammatory drugs. Particular attention is paid to the effectiveness and safety of pharmacological treatment of pain and inflammatory syndromes in rheumatic diseases.